PENGUKURAN RISIKO ASET TEKNOLOGI INFORMASI BERBASIS PBI PADA SEKTOR PERBANKAN DI INDONESIA - Harahap, Rudy M; Subita, Marisa Caroline; Octavia, Shinta (Bina Nusantara University, 2009)
In the globalization era, information technology (IT) plays an important role in the daily corporate operation. However, there are some risks in the IT implementation. To minimize these risks, a corporate should have an IT risk management. The objective of this research is to measure IT asset risks in Indonesia banking sector. The focus of this research is the IT risks, control, and risk mitigation. The research data is processed by Risk Register Table, based on Bank Indonesia Regulation (PBI). The measurement shows the risks trend rate is not too high. However, there is a need to minimize the risks. To minimize the risks, the measurement results could be used. The minimization of IT risks could improve the bank services to its users.Keywords: risk measurement, IT asset risk, Bank Indonesia Regulation (PBI)